Hrafnkel or the ambiguities - Miller, William Ian (Oxford University Press, 2017)
William Ian Miller presents a close reading of one of the best known of the Icelandic sagas, showing its moral, political, and psychological sophistication. 'Hrafnkel' tells of a fairly simple feud in which a man rises, falls, and rises again with a vengeance, so to speak. The saga deals with complex issues with finely layered irony: who can one justifiably hit, when, and by what means? It does this with cool nuance, also taking on matters of torture and pain-infliction as a means of generating fellow-feeling. How does one measure pain and humiliation so as to get even, to get back to equal? People are forced to set prices on things we tell ourselves soporifically are priceless, such as esteem, dignity, life itself. Morality no less than legal remedy involves price-setting. This book flies in the face of all the previous critical literature which, with very few exceptions, imposes simplistic readings on the saga. A translation of the saga is provided as an appendix
Keywords: Revenge in literature; Honor in literature; Law in literature; Sagas